PHYSICAL EXERCISE AS A NON-PHARMACOLOGICAL TREATMENT FOR PEOPLE WITH FIBROMYALGIA (International Seven Journal of Health Research, 2024)
Fibromyalgia is a chronic disease with a limited and challenging lack of concrete scientific information, since it is a pathology that is difficult to diagnose, which is often confused with other diseases and because it does not present proven evidence about its real appearance, affecting more the female gender. Physical exercise can be an alternative to promote the improvement of quality of life and independence (motor autonomy) in people with Fibromyalgia, in addition to possibly positively impacting individuals in many other aspects. The decrease in the use of pharmacological resources may be a beneficial consequence of the use of physical exercises in a systematic way. This review aimed to demonstrate the effects of physical exercise in patients diagnosed with fibromyalgia. According to the surveys conducted, scientific studies prove that the practice of physical exercise regularly and with adequate monitoring by a professional is effective and helps to reduce pain points (tender points), reduce the use of pharmacological resources, and improve quality of life.